Worsening renal function, adverse clinical events and major determinants for changes of renal function in patients with atrial fibrillation: a Japanese multicenter registry substudy. (2nd November 2019) - Kuronuma, Keiichiro; Okumura, Yasuo; Yokoyama, Katsuaki; Matsumoto, Naoya; Tachibana, Eizo; Oiwa, Koji; Matsumoto, Michiaki; Kojima, Toshiaki; Haruta, Hironori; Nomoto, Kazumiki; Sonoda, Kazumasa; Arima, Ken; et al.
Abstract: Objective: To explore factors related to changing renal function and the prognostic effect of worsening renal function in patients with atrial fibrillation (AF). Methods: The present substudy was based on the SAKURA AF Registry, a Japanese multicenter prospective observational registry that includes 3267 AF patients from 63 institutions in the Tokyo area. Worsening renal function was defined as an estimated glomerular filtration rate (eGFR) decrease equaling more than 20% of the patient's baseline eGFR. Results: During a median 39.3 month follow-up period, patients' eGFR decreased annually by a mean value of 1.07 mL/min/1.73 m 2 . Multivariable analysis showed that age ≥75 years, body weight ≤50 kg, a history of heart failure and initially preserved renal function (creatinine clearance [CrCl] ≥ 60 mL/min) were significantly associated with a decrease in eGFR, whereas a history of AF ablation was associated with a maintain in eGFR. The 194 patients with worsening renal function were at significantly increased risk of death, stroke and major bleeding (adjusted hazard ratios [HRs]: 2.06, 1.97 and 2.23, respectively). Conclusion: Age ≥75 years, body weight ≤50 kg, a history of heart failure and initially preserved renal function appear to promote renal dysfunction in patients with AF, but a history of AF ablation seems to have a favorable effect. Worsening renal function seems to increase AF patients' risk of adverse clinical events. Renal function can decline quickly; thus, early intervention including AF ablation is warranted.